BRIDGING EMPOWERMENT AND ENTREPRENEURSHIP: HOW NGOS FOSTER WOMEN'S SUCCESS IN EGYPT'S TOURISM INDUSTRY - Kareem A. RASHWAN; Viju MATHEW; Reem AKEF; Ahmed Mohamed ELBAZ (Geo Journal of Tourism and Geosites)
The study investigates the role of NGOs in empowering women by mediating women's entrepreneurship. The study adopted a quantitative approach with a total of 125 females involved in the United Nations Women (UNW) program in Egypt. The study employed Partial Least Squares Structural Equation Modelling (PLS-SEM) to test the proposed conceptual framework. The results show that NGO programs have a positive and significant impact on empowering women psychologically, socially, politically, and economically through the mediating role of entrepreneurship. The study suggests practical ways for policymakers and tourism scholars to assist women in their tourism entrepreneurship.